Analysis of Handoff Communication Using SBAR (Situation, Background, Assessment, Recommendation) in Emergency Department and Intensive Care Unit: A Scoping Review - Azmi, Nur; Prawesti Priambodo, Ayu; Nuraeni, Aan (Media Publikasi Cendekia Indonesia, 2025)
Communication between health workers is crucial in providing nursing care and improving patient safety. Communication problems can cause incidents that lead to disability or death. This study aimed to identify the implementation of handoff communication using sbar in the emergency department and intensive care unit. This review used a scoping review design that uses the Arksey and O'Malley framework. Article searches through two databases, namely Sciencedirect and Pubmed, and the search engine, Google Scholar. The keywords used were